(untitled) (World Bulletin of Public Health, 2024)
This article presents literature data on the incidence, causes, pathogenesis and pathomorphological types of hypertrophic and polypous rhinitis. Chronic hypertrophic and polypous rhinitis is a process of neoplastic growth of tissues, in which both parenchyma and stromal structures proliferate simultaneously. Exogenous and endogenous factors that cause a vasomotor reaction in the mucous membrane are distinguished as causes. Exogenous influences include cold, factors that provoke reflexes, smoke, sharp and spicy foods, meteomils, and various drugs, which have a vasoconstricting and hypotensive effect. Among the endogenous factors, hormonal dysfunction, endocrine diseases and physical psychoemotional effects gain great importance. Morphologically, simple, allergic and fibromatous types of this disease are distinguished.